ELECTROLYTE IMBALANCE TRIGGERING RELAPSE OF INFLAMMATORY NEUROPATHY. Issue 11 (9th October 2013) - Keshavan, A; Gandhi, S; Lunn, MP; Reilly, MM
Abstract : Electrolyte imbalance is a well–known cause of acute neurological deterioration in the central and peripheral nervous systems. Rapid correction of hyponatraemia1 can cause central pontine myelinolysis, and in muscle tetany may result from hypocalcaemia. However the role of electrolyte imbalance in peripheral neuropathy although well–described is encountered less frequently. We describe a case of a 71 year old female with a fourteen year history of chronic inflammatory demyelinating polyneuropathy (CIDP) and stable monoclonal gammopathy, normally maintained on three–weekly intravenous immunoglobulin (IVIG) therapy. At her best baseline, she has a normal motor examination and reduced vibration sense only to the ankles. She presented with a four week history of progressive numbness and paresthesiae in all four limbs, reduced balance, a decline in mobility with frequent falls and reduced hand function. The deterioration developed after a week of non–bloody diarrhoea with night sweats but continued to progress through two courses of her regular IVIG. She also had a past history of breast cancer, hypertension and a duodenal ulcer. On examination she had a profound sensory ataxia and pseudo–athetosis of the upper limbs. Power was preserved. Pinprick was reduced to the forearm and thighs. Vibration sense was present only at the sternum. Proprioception was reduced to the shoulders and hips. She was areflexic. General examination was normal. Blood investigations showed hypomagnesaemia of 0.1 (range 0.6–1.0), hypocalcaemia of 1.75 (range 2.15–2.55), mild hypokalaemia of 3.2 (range 3.5–5.1) but stable renal function. Nerve conduction studies showed a length–dependent demyelinating sensorimotor neuropathy with significant deterioration from previous studies. Her paraprotein level was stably low. Thus we considered the metabolic disturbance as a potential cause of her acute severe relapse of her CIDP. The diarrhoea resolved spontaneously and potassium and calcium levels normalised after oral treatment. However the hypomagnesaemia required high–dose oral and intravenous supplementation. Investigations for a malabsorption syndrome were negative. She was taking two medications known to be associated with hypomagnesaemia. After stopping indapamide, a thiazide–like diuretic, her urine magnesium output was low, so a renal cause was unlikely. Omeprazole, which had been doubled in the last year after the diagnosis of her duodenal ulcer, is known in multiple case series to be associated with severe symptomatic hypomagnesaemia that is thought to be a class effect of proton pump inhibitors (PPIs). 2 This prompted us to halve the dose of omeprazole. Her serum magnesium level stabilised in the low–to–normal range and she was treated with two further courses of 2 g/kg IVIG. She had a marked improvement in sensory examination and functional ability. Her proprioceptive loss and sensory ataxia resolved. A logical approach to investigating for reversible causes for her deterioration pointed to drug–induced hypomagnesaemia as a potentially important cause of acute decompensation in CIDP. Her severe relapse remained refractory to treatment until her metabolic disturbance was normalised, after which she showed an excellent response.